Worry impairs the problem-solving process: Results from an experimental study. (December 2020) - Llera, Sandra J.; Newman, Michelle G.
Abstract: Introduction: Many individuals believe that worry helps solve real-life problems. Some researchers also purport that nonpathological worry can aid problem solving. However, this is in contrast to evidence that worry impairs cognitive functioning. Objective: This was the first study to empirically test the effects of a laboratory-based worry induction on problem-solving abilities. Procedure: Both high ( n  = 96) and low ( n  = 89) trait worriers described a current problem in their lives. They were then randomly assigned to contemplate their problem in a worrisome ( n  = 60) or objective ( n  = 63) manner or to engage in a diaphragmatic breathing task ( n  = 62). All participants subsequently generated solutions and then selected their most effective solution. Next, they rated their confidence in the solution's effectiveness, their likelihood to implement the solution, and their current anxiety/worry. Experimenters uninformed of condition also rated solution effectiveness. Results: The worry induction led to lower reported confidence in solutions for high trait worry participants, and lower experimenter-rated effectiveness of solutions for all participants, relative to objective thinking. Further, state worry predicted less reported intention to implement solutions, while controlling for trait worry. Finally, worrying about the problem led to more elevated worry and anxiety after solving the problem compared to the other two conditions. Conclusions: Overall, the worry induction impaired problem solving on multiple levels, and this was true for both high and low trait worriers. Highlights: Worrying about a personal problem lowered confidence in solutions for high trait worriers. Thinking objectively about a problem led to more effective solutions than worrying or focused breathing. State worry predicted less intention to implement solutions, while controlling for trait worry. Worrying beforehand led to elevated worry and anxiety after solving a personal problem.